2017
DOI: 10.1002/jctb.5297
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of an yttrium europium oxide phosphor from waste fluorescent tubes using a Brønsted acidic ionic liquid, 1‐methylimidazolium hydrogen sulfate

Abstract: Background: Spent fluorescent lamps, classified as hazardous waste in the EU, are segregated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Then, a series of physical processes (i.e., crushing, sweeping and sorting) is carried out to liberate individual material streams. The fluorescent powder containing phosphors is blown out from the glass surface by high-pressure air and heated at about 450 • C to remove mercury through desorption and distillation [9,58]. The only valuable material flows recovered are metals (e.g., aluminum), the glass and the electronic components.…”
Section: Potentials For End-of-life Recovery and For Closing The Euromentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a series of physical processes (i.e., crushing, sweeping and sorting) is carried out to liberate individual material streams. The fluorescent powder containing phosphors is blown out from the glass surface by high-pressure air and heated at about 450 • C to remove mercury through desorption and distillation [9,58]. The only valuable material flows recovered are metals (e.g., aluminum), the glass and the electronic components.…”
Section: Potentials For End-of-life Recovery and For Closing The Euromentioning
confidence: 99%
“…Additional momentum to collection and process efficiency could also derive from a growing interest in securing the supply of critical materials like europium. Spent fluorescent lamps are predicted to contain up to 25,000 t of REEs by 2020 [58], so the existence of management schemes for fluorescent lamps at end-of-life could supply substantial amounts of europium scrap and foster the implementation of dedicated recovery and recycling practices for europium. Industry and academia are exploring processes for the recycling of REEs from spent phosphors, which might impact future supply-demand dynamics of europium.…”
Section: Potentials For End-of-life Recovery and For Closing The Euromentioning
confidence: 99%
“…Miquel et al [22] VOCs have been shown to have good solubility in some ILs, the application of these absorbents for VOCs removal has received little attention. A particular advantage of the use of ILs in absorbent methodologies is that in many applications they have been shown to be easily recycled for multiple reuse in a number of processes [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphor emits luminescence when activated by photons, and makes the colorful screen . Phosphors contain yttrium–europium compound (Y 2 O 2 S:Eu 3+ ) for red color, zinc sulfide–copper (ZnS:Cu) for green color and zinc sulfide–silver (ZnS:Ag) for blue color . Yttrium (Y) and europium (Eu) are rare earth elements (REEs) that have been categorized as technology‐critical elements (TCEs) because of their wide uses in electronic devices and their high and imminent risk of supply interruption .…”
Section: Introductionmentioning
confidence: 99%
“…5 Phosphors contain yttrium-europium compound (Y 2 O 2 S:Eu 3+ ) for red color, zinc sulfide-copper (ZnS:Cu) for green color and zinc sulfide-silver (ZnS:Ag) for blue color. 6,7 Yttrium (Y) and europium (Eu) are rare earth elements (REEs) that have been categorized as technology-critical elements (TCEs) because of their wide uses in electronic devices and their high and imminent risk of supply interruption. [8][9][10] The global reserves of yttrium oxide and europium oxide were estimated to be around 500 000 tons and 150 000 tons, respectively, while their global consumptions were 5000-7000 tons and 100 tons per year and increased every year.…”
Section: Introductionmentioning
confidence: 99%